Factors Affecting Company Values in the Companies Listed in the Jakarta Islamic Index - Himmati, Risdiana; Nabila, Rifda; Maslinda, Lisza May (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2021)
The rapid development of the global economy has triggered competition between economic actors, especially between companies; therefore, it is necessary to do the company value analysis to attract investors. The purpose of this study was to determine the factors that affect firm value. This study used a quantitative approach, with a sample of 3 companies. The data processing used Error Correction Model analysis. The study results partially showed that the relationship between the company value in the short and long term with the company size had a negative and insignificant effect; the company growth had a positive and insignificant effect. In the short term, the funding decisions had a negative and insignificant effect; the profitability had a positive and insignificant effect; the investment decisions had a positive and insignificant effect. In the long term, the funding decisions had a positive and significant effect, the profitability had a negative and insignificant effect, and the investment decisions had a positive and significant effect. Simultaneously the independent variable affects the firm value. These findings have implications for adding to the literature on the factors that influence company values and are valuable for executives in companies, especially in implementing policies to increase company value.